Fabrication and simulation analysis of flexible polymethylsilsesquioxane (PMSQ) aerogels by using dimethyl sulfoxide (DMSO) as solvent. (5th July 2019) - He, Fei; Zhou, Liang; Fang, Minhan; Sui, Chao; Li, Wenjie; Yang, Lijuan; Li, Mingwei; He, Xiaodong
Abstract: The flexible bulk polymethylsilsesquioxane (PMSQ) aerogels were synthesized using DMSO as solvent via the sol-gel process and supercritical drying. The porous microstructures and the bonding linkage were investigated by means of Fourier transform infrared (FT-IR) spectra, nitrogen adsorption-desorption method and scanning electron microscopy (SEM). The effects of dimethyl sulfoxide (DMSO) and ammonium hydroxide (AH) in sol-gel process were discussed. The results show that the micro-morphology of PMSQ aerogels is an expression of freezing siloxane system by adjusting the relative ratio of DMSO and AH. The PMSQ aerogels are provided with high specific surface area, low density, favorable flexibility and low thermal conductivity. The multi-scale simulative analysis reveals that DMSO as solvent tends to uniformly disperse M-monomer due to similar solubility parameter (SP) and repulsion parameter (RP). SP and RP can be regarded as important parameters of solvent selection to explain and predict gel compatibility and uniformity. Graphical abstract: Unlabelled Image Highlights: The flexible bulk polymethylsilsesquioxane (PMSQ) aerogels were synthesized by using dimethyl sulfoxide (DMSO) as solvent. The PMSQ aerogels present interconnected network-like skeletons by adjusting the ratio of DMSO and ammonium hydroxide. The PMSQ aerogels have high specific surface area, low density, favorable flexibility and low thermal conductivity. Solubility parameter and repulsion parameter can be used to explain uniform dispersion of solute monomer in DMSO solvent.